Perception of University Social Responsibility in the Faculty of Economic Engineering, Statistics and Social Sciences of the National University of Engineering 2019. - Quiroz Vera, Eduardo Fernando (2019)
This research was carried out at the Faculty of Economic, Statistical and Social Sciences Engineering (FIEECS) of the National University of Engineering (UNI), it was established as a general objective: to identify the perception of the educational actors of the FIEECS UNI regarding 4 dimensions of university social responsibility: Responsible campus, Professional and citizen training, Social knowledge management and Social participation. The research was based on the theoretical model of University Social Responsibility (Vallaeys, de la Cruz, & Sasia, 2009). The University Social Responsibility (RSU) instruments with Likert type scaling were applied. It is concluded that in the Responsible Campus dimension, students, teachers and administrators distin-guish negative elements in the indicators of environment, transparency and democracy, communication and marketing. In relation to professional and citizen training, teachers recognize the needs of the institution in the indicators: Integration of external social actors in the design of curricular meshes, Articulation between professionalization and solidarity volunteering and Presence of citizen and social responsibility issues in the curriculum With regard to Social knowledge management, research teachers identify weaknesses in the indicators: Dissemination and transfer of socially useful knowledge to disadvantaged audiences, Promotion of research applied to development issues and Integration of external social actors in research.